Conducting ink based on cellulose nanocrystals and polyaniline for flexographical printing. Issue 46 (20th November 2017) - Latonen, R.-M.; Määttänen, A.; Ihalainen, P.; Xu, W.; Pesonen, M.; Nurmi, M.; Xu, C.
Abstract : A highly conducting water-based ink composed of cellulose nanocrystals and polyaniline was prepared for flexographical printing by the emulsion polymerization approach. Abstract : A water-based environmentally friendly electrically conducting ink composed of cellulose nanocrystals (CNC) and polyaniline (PANI) was prepared. PANI was synthesized by the emulsion polymerization approach using dodecylbenzenesulfonic acid (DBSA) as the dopant to induce spherical nanoparticulate formation. Glycerol was used to adjust the viscosity of the ink. The CNC–PANI ink was characterized by transmission electron microscopy, UV-visible spectroscopy and viscosity measurements. The ink was successfully printed on multilayer curtain coated paper by the flexographical printing method. The printed layers were characterized by optical and atomic force microscopy techniques and cyclic voltammetry. A stable nanoparticulate CNC–PANI ink with an electrical conductivity of the printed films between 30 and 60 S cm −1 was obtained which was more than an order of magnitude higher than for the corresponding film without CNC.